Investigation of Cellular Base Transmitter Station Power Radiation using Spectrum Analyzer - Muhammad Hamka Ibrahim; Subuh Pramono (Journal of Electrical, Electronic, Information, and Communication Technology, 2022)
The development of information and communication technology has spurred the development of the world of telecommunications. The development of telecommunications can be seen from the number of cellular service users supported by technological infrastructure in the form of BTS (Base Transmission Station). But in its development, there are social problems in the form of resistance from the community around BTS, one of the things that people worry about is the danger of radiation from BTS. This could be due to a lack of socialization and knowledge from the community. This study aims to provide education as well as quantitative evidence regarding radiation from BTS in Bulakrejo which is compared with safety standards from International Commission on Non-Ionizing Radiation Protection (ICNIRP) and Ministry of Communication and Information Indonesia. The result of investigation shows that received Power Radiation in near Base Station is safe according to regulatory standard.